2017
DOI: 10.1101/224428
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping the phenotypic repertoire of the cytoplasmic 2-Cys peroxiredoxin – thioredoxin system. 1. Understanding commonalities and differences among cell types

Abstract: The system (PTTRS) formed by typical 2-Cys peroxiredoxins (Prx), thioredoxin (Trx), Trx reductase (TrxR), and sulfiredoxin (Srx) is central in antioxidant protection and redox signaling in the cytoplasm of eukaryotic cells. Understanding how the PTTRS integrates these functions requires tracing phenotypes to molecular properties, which is non-trivial. Here we analyze this problem based on a model that captures the PTTRS’ conserved features. We have mapped the conditions that generate each distinct response to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 100 publications
0
13
0
Order By: Relevance
“…The analysis in ref. [43] predicts that in cells with abundant peroxiredoxin reduction capacity and limited alternative H 2 O 2 sinks the peroxiredoxin/thioredoxin/sulfiredoxin system shows bi-stability and hysteresis. The simulations in Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis in ref. [43] predicts that in cells with abundant peroxiredoxin reduction capacity and limited alternative H 2 O 2 sinks the peroxiredoxin/thioredoxin/sulfiredoxin system shows bi-stability and hysteresis. The simulations in Figs.…”
Section: Discussionmentioning
confidence: 99%
“…32 However, the Prxs are of great importance for regulation of signaling cascades that are modulated by H 2 O 2 , lipid hydroperoxides, or peroxynitrite. Modeling of the activities of the Prxs-Trxs-TrxR1 (and Srx) system has suggested their synergetic coupling in cells 116,126 and strongly correlated with their protein concentrations and activities in 10 different tumor cell lines. 116 The net result is to maintain redox homeostasis with the Prx-SS reduction capacity in slight excess over the maximal steady state level of Prx-SS production.…”
Section: The Trxrs and Their Critical Role In Redox Homeostasismentioning
confidence: 99%
“…Modeling analysis further indicated that at low oxidative loads (in the nanomolar range) the 2-Cys Prxs consume approximately 99% of the H 2 O 2 in the cytosol with TrxR/Trx also adequately sufficient to maintain Prx function. In turn, GPx1 is much less active than TrxR, 116 has a lower affinity for H 2 O 2 (K m of 20 μM) 26,32 and thus GPx is unable to sense nanomolar H 2 O 2 concentrations. Consequently, it has been predicted that GPx typically consumes less than 0.2% of the H 2 O 2 under basal, nonoxidative stress conditions.…”
Section: The Trxrs and Their Critical Role In Redox Homeostasismentioning
confidence: 99%
See 2 more Smart Citations